The Feudal Lords of Lahore’s stock exchange - Mohamed, Noor; Hassan, Arif (GSM, IIUM, 2010)
The case provides a good example of the challenges that an expatriate manager may face abroad. In the backdrop of the socio-cultural and political realities, the case presents the experience of a Malaysian expatriate who was appointed as a CEO of a joint venture brokerage company in Pakistan. The CEO was assigned the task of infusing vitality and turning around this loss-making company. The CEO experienced several shocking cultural differences and unethical and clandestine practices in the organization. The chief architect behind all these feudal and corrupt practices was the man who had been working as a General Manager for a long time. The Malaysian CEO patiently studied the organizational culture and practices and introduced several cultural and structural changes. He also tried to plug holes in the daily operations and put an end to the corrupt practices seemingly going on for some time. That sounded the alarm bell to the Pakistani GM and through political manoeuvring, he was able to create a situation where the Malaysian CEO had to leave the country in a huff thus stalling all the change process initiated by him.